Genealogy of Religious Experience in Studies of religiosity - Alireza Shojaeezand (Taḥqīqāt-i Farhangī-i Īrān, 2009)
As a fascinating issue for the scholars in Religion Studies, religious experience has a long-lasting theological and social background in Christianity and Occidental history which has caused to the present increasing attention to the matter. However, as other concepts ad categories, its development in Iran has experienced a distorted process of just Academic and theoretical debates and not to experience it practically. Avoiding evaluating the term from Islamic theological point of view, while introducing some of its theological or historical and social backgrounds in the west, I attempt to make theologists and philosophers of religion, in addition to the religious psychologists and sociologists pay more attention to the necessity of caution and focus on the nature and status of religious Experience in Religion Studies, and its relation with religiosity.